2022
DOI: 10.1007/s13730-021-00677-9
|View full text |Cite
|
Sign up to set email alerts
|

New-onset kidney biopsy-proven IgA vasculitis after receiving mRNA-1273 COVID-19 vaccine: case report

Abstract: As mRNA COVID-19 vaccines have become widely available, cases of new-onset glomerular disease after receiving COVID-19 vaccination have been reported. Here, we present a case of kidney biopsy-proven new-onset IgA vasculitis after receiving the mRNA-1273 (Moderna) COVID-19 vaccination. A 47-year-old man with a 10-year medical history of hypertension and hyperuricemia visited our hospital 19 days after receiving an initial mRNA-1273 COVID-19 vaccine injection for purpuric eruption on the legs and dorsal regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…In the second selection round, full-text articles of the remaining papers were assessed. For the final analysis, we retained 67 reports [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , <...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the second selection round, full-text articles of the remaining papers were assessed. For the final analysis, we retained 67 reports [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , <...…”
Section: Resultsmentioning
confidence: 99%
“…Data are presented as frequency or as median with interquartile range. All Berger Glomerulo-nephritis Henoch-Schönlein Vasculitis P-value N 87 47 40 Males: females, N 45:40 20 : 25 25 : 15 0.128 Age years 34[ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] ] 35 [ [19] , [20] , [21] , [22] , [23] , [24] ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies have reported the incidence of new-onset and relapse of nephrotic syndrome (NS) following COVID-19 vaccination in patients with glomerular diseases, especially those with minimal change disease (MCD) [ 8 14 ]. Furthermore, several studies have reported the incidence of gross hematuria following COVID-19 vaccination in patients with immunoglobulin A nephropathy (IgAN) [ 15 17 ] and IgA vasculitis [ 18 ]. Most recently, a clinical survey of gross hematuria associated with COVID-19 vaccination using a web-based questionnaire in Japan reported the clinical features of gross hematuria in 27 patients following COVID-19 vaccination [ 19 ].…”
Section: Introductionmentioning
confidence: 99%